Bothrops moojeni snake venom induces an inflammatory response in preadipocytes: Insights into a new aspect of envenomation. - Rodrigo Maia-Marques; Danilo Santos Teixeira; Priscila Motta Janovits; Carlos DeOcesano-Pereira; Elbio Leiguez; Catarina Teixeira (Public Library of Science (PLoS), 2022)
Bothrops envenomation is a public health problem in Brazil. Despite the advances in the knowledge of the pathogenesis of systemic and local effects induced by Bothrops venom, the target tissues to this venom are not completely characterised. As preadipocytes are important cells of the adipose tissue and synthesize inflammatory mediators, we investigated the ability of B. moojeni snake venom (Bmv) to stimulate an inflammatory response in 3T3-L1 preadipocytes in vitro, focusing on (1) the release of PGE2, IL-6, TNF-α, MCP-1, KC, leptin and adiponectin; (2) the mechanisms involved in PGE2 release and (3) differentiation of these cells. Cytotoxicity of Bmv was determined by MTT assay. The concentrations of PGE2, cytokines and adipokines were quantified by EIA. Participation of the COX-1 and COX-2 enzymes, NF-κB and PGE2 receptors (EP1-4) was assessed using a pharmacological approach, and protein expression of the COX enzymes and P-NF-κB was analysed by western blotting. Preadipocyte differentiation was quantified by Oil Red O staining. Bmv (1 μg/mL) induced release of PGE2, IL-6 and KC and increased expression of COX-2 in preadipocytes. Basal levels of TNF-α, MCP-1, leptin and adiponectin were not modified. Treatment of cells with SC560 (COX-1 inhibitor) and NS398 (COX-2 inhibitor) inhibited Bmv-induced PGE2 release. Bmv induced phosphorylation of NF-κB, and treatment of the cells with TPCK and SN50, which inhibit distinct NF-κB domains, significantly reduced Bmv-induced PGE2 release, as did the treatment with an antagonist of PGE2 receptor EP1, unlike treatment with antagonists of EP2, EP3 or EP4. Bmv also induced lipid accumulation in differentiating cells. These results demonstrate that Bmv can activate an inflammatory response in preadipocytes by inducing the release of inflammatory mediators; that PGE2 production is mediated by the COX-1, COX-2 and NF-κB pathways; and that engagement of EP1 potentiates PGE2 synthesis via a positive feedback mechanism. Our findings highlight the role of the adipose tissue as another target for Bmv and suggest that it contributes to Bothrops envenomation by producing inflammatory mediators.